The Effect of Deep Breathing Relaxation on Reducing Preoperative Anxiety in C-Section Patients - Nurningsih S.A Karim; Sulistiyah Sulistiyah (Jurnal Siti Rufaidah, 2025)
Preoperative anxiety is common among women scheduled for cesarean section (C-section), affecting surgical outcomes, recovery, and bonding. This study investigated the effect of guided deep breathing relaxation on reducing preoperative anxiety in C-section patients. A quasi-experimental design with a pretest-posttest control group was conducted with 30 participants from [Name of Hospital]. Participants were randomly assigned to an intervention group (n = 15), which practiced deep breathing exercises 30 minutes before surgery, and a control group (n = 15) receiving standard care. Preoperative anxiety was assessed using the State-Trait Anxiety Inventory (STAI) before and after the intervention. Results showed a significant decrease in anxiety scores in the intervention group (from 45.2 ± 6.3 to 33.5 ± 5.8, p < 0.001), while the control group showed minimal change (44.8 ± 5.9 to 43.6 ± 6.1, p = 0.124). Post-intervention comparisons revealed a significant difference between groups (t = 7.21, p < 0.001). These findings indicate that guided deep breathing effectively reduces preoperative anxiety in C-section patients, suggesting it as a simple, safe, and cost-effective intervention that can improve maternal psychological well-being and surgical readiness. This non-pharmacological approach may also contribute to better postoperative outcomes.